Creating the Framework for Cross-Sector Health Analysis for Local Communities - Richards, Heather; Varas, Kim; Magnus, Samantha; Oh, Jinhwa; Voggenreiter, Christine (International Journal of Population Data Science, 2018)
Introduction A newly developed BC Ministry of Health geography classification has enabled a standardized approach for community-level analysis of health needs and service provision. An innovative methodology was developed and applied to health administrative data, creating more opportunities to identify variations in health status and utilization across the health system. Objectives and Approach Two design principles informed the development of the new geographies. Firstly, they reflect where people live and the communities with which they identify, and secondly, they will assist with identifying where health services are needed for local populations. The objective was to provide the Ministry and health authorities with a framework to identify and work towards providing the optimal delivery of services at the local level. A working group was established for this project and included representatives from the Ministry, each regional health authority, Provincial Health Services Authority, First Nations Health Authority, and BC Stats. Results The building block for the geography classification is the Census Dissemination Block, the lowest unit of geography available in the Standard Geography Classification maintained by Statistics Canada. The geographies were assigned urban-rural designations based on an algorithm that considered the presence of a population centre, the size of the population centre, and the proportion of the population living in it, among other aspects. One of the main goals of the urban-rural designations was to provide meaningful peer groups for cross-jurisdictional studies. The project also reengineered the methods to geocode addresses to improve accuracy to use street addresses (over past method that used postal codes) so that assignment to Census Dissemination Block would be precise. The end result was 218 community geographies with urban-rural designations. Conclusion/Implications This geography standard allows health system stakeholders to better understand of geographic variation in utilization and access to health care. The ability to link and share information to profile community health between health administrative data and Census data available from Statistics Canada is better due to improved geocoding of addresses.